Dynamics of quantum gas in non-abelian gauge field - Hasan, Mehedi (Nanyang Technological University, 2021)
Experimental observation of Zitterbewegung is considered a holy grail of the modern physics since its debut in 1930 by Schr odinger. In this thesis we describe the  first experimental observation of this effect in a two-dimensional ultracold atomic wave packet. In addition to that, we have also revealed the anisotropic of nature of Zitterbewegung, in the presence of non-Abelian Gauge  field. To observe this e ect, we have performed laser cooling in two major steps 461 nm magneto-optical trap (MOT) and 689 nm MOT and then loaded the atoms into an optical dipole trap. After performing optical pumping to one of the Zeeman states of the hyper ne ground-state, while atoms are inside the dipole trap, we have cooled down the strontium-87 atoms via evaporativ cooling and the gas enters the quantum regime at a T/T_F = 0.21(4), with Temperature T and Fermi temperature T_F. As the temperature of the gas (40-50 nK) is far below the recoil temperature(230 nK) of the atoms, we have performed experiments with the wave packet that reveals the envisaged Zitterbewegung effect. In order to demonstrate the anisotropy of the Zitterbewegung, we introduced a kick to the cold atomic wave packet so that the wave packet explores the momentumdependence of the energy eigenstates of the dressed Hamiltonian. We reveal the complete anisotropic nature of the Zitterbewegung amplitude and the relation of the oscillation frequency with the energy-gap between the two bands. We speculate that this could be a new way to map the band-diagram of a multi-band system. All the results are analyzed and explained with analytic calculations coupled with numerical analysis.